Scientific dishonesty—questionnaire to doctoral students in Sweden - Nilstun, Tore (Journal of medical ethics, 2010)
‘Scientific dishonesty’ implies the fabrication, falsification or plagiarism in proposing, performing or reviewing research or in reporting research results. A questionnaire was given to postgraduate students at the medical faculties in Sweden who attended a course in research ethics during the academic year 2008/2009 and 58% answered (range 29%-100%). Less than one-third of the respondents wrote that they had heard about scientific dishonesty in the previous 12 months. Pressure, concerning in what order the author should be mentioned, was reported by about 1 in 10 students. We suggest that all departments conducting research should have a written policy about acceptable research behaviour and that all doctoral students should be informed of the content of this policy. Participants in the research groups concerned should also be required to analyse published articles about scientific dishonesty and critically discuss what could be done about unethical conduct.